Karakteristik Bakteri Endofit Akar Tanaman Kedelai Penghasil Hormon Tumbuh IAA - Afifah Mariana; Agus Irianto; Iman Budisantoso (Biotropic : The Journal of Tropical Biology, 2023)
The increase in soybean production and productivity has become a significant focus in the effort to meet global food demands. The use of environmentally friendly agricultural technologies and practices is a vigorously pursued strategy. Endophytic bacteria are one of the potential bioagents that can stimulate plant growth. The ability of endophytic bacteria to synthesizing the plant hormone indole-3-acetic acid (IAA) can be an alternative in the effort to enhance soybean plant productivity and ensure long-term agricultural sustainability. The objective of this study is to analyze diversity and ability of endophytic bacteria isolated from soybean roots to produce IAA. This research was conducted through several stages, including the isolation of endophytic bacteria from soybean root, evaluating the isolates' ablity  for IAA production, and characterizing potential isolates based on macroscopic and microscopic characteristics. This research indicated that a total of 11 endophytic bacteria isolates were obtained from soybean plant roots. Among them, four isolates, namely EAK4, EAK5, EAK6, and EAK8, demonstrated the capability to synthesizing IAA ranging from 35.46 to 44.56 ppm. These isolates showed various macroscopic and microscopic characteristics and hold promise as biological agents that promote planth growth.